LINGUISTIC FEATURES AND PRESENTATION OF MATERIALS ON ENGLISH TEXTBOOK “WHEN ENGLISH RINGS A BELL” BASED ON BSNP - Hilda Zubaidah; Gustaman Saragih (Universitas Indraprasta PGRI, 2022)
The textbooks play an important role in teaching and learning activity in language program. Because of the various textbooks provided, textbook analysis is seen as an important thing to be conducted in order to find out how the components of the textbook are served. This study was aimed to investigate to what extent the English textbook entitled “Bahasa Inggris: When English Rings a Bell” for eighth grade students meet the criteria of BSNP (linguistic features and presentation of materias). The linguistic features consist of language appropriateness while the presentation of materials consist of content appropriates, presentation appropriateness, and graphic appropriateness. This study was descriptive qualitative approach. The instrument used to collect the data is document study used in the form of checklist. A checklist was made adopted from BSNP (2011) framework. The results of this study showed that textbook entitled “When English Rings a Bell” for Eight Grade is suitable to be used in teaching learning process. The textbook achieved the fulfilment score of language appropriateness (100%), content appropriateness (81,25%), presentation appropriateness (88,89%), and graphics appropriateness (97,64%). This book is categorized “good” textbook by achieving the score of 95,07%. Thus, it can be concluded that textbook is suitable to be used in order to help the teaching learning process in the classroom with the help of other sources and teacher improvisation.